Search for anomalous couplings in boosted WW/WZ→ℓνqq‾ production in proton–proton collisions at s=8 TeV - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Asilar, Ece; Bergauer, Thomas; Md. Ali, Mohd. Adli (Elsevier, 2017)
This Letter presents a search for new physics manifested as anomalous triple gauge boson couplings in WW and WZ diboson production in proton–proton collisions. The search is performed using events containing a W boson that decays leptonically and a W or Z boson whose decay products are merged into a single reconstructed jet. The data, collected at √s = 8 TeV with the CMS detector at the LHC, correspond to an integrated luminosity of 19 fb−1. No evidence for anomalous triple gauge couplings is found and the following 95% confidence level limits are set on their values: λ ([−0.011, 0.011]), κγ ([−0.044, 0.063]), and gZ 1 ([−0.0087, 0.024]). These limits are also translated into their effective field theory equivalents: cWWW/ 2 ([−2.7, 2.7] TeV−2), cB/ 2 ([−14, 17] TeV−2), and cW/ 2 ([−2.0, 5.7] TeV−2).